Topical Apigenin Alleviates Cutaneous Inflammation in Murine Models. (19th November 2012) - Man, Mao-Qiang; Hupe, Melanie; Sun, Richard; Man, George; Mauro, Theodora M.; Elias, Peter M.
Abstract : Herbal medicines have been used in preventing and treating skin disorders for centuries. It has been demonstrated that systemic administration of chrysanthemum extract exhibits anti-inflammatory properties. However, whether topical applications of apigenin, a constituent of chrysanthemum extract, influence cutaneous inflammation is still unclear. In the present study, we first tested whether topical applications of apigenin alleviate cutaneous inflammation in murine models of acute dermatitis. The murine models of acute allergic contact dermatitis and acute irritant contact dermatitis were established by topical application of oxazolone and phorbol 12-myristate 13-acetate (TPA), respectively. Inflammation was assessed in both dermatitis models by measuring ear thickness. Additionally, the effect of apigenin on stratum corneum function in a murine subacute allergic contact dermatitis model was assessed with an MPA5 physiology monitor. Our results demonstrate that topical applications of apigenin exhibit therapeutic effects in both acute irritant contact dermatitis and allergic contact dermatitis models. Moreover, in comparison with the vehicle treatment, topical apigenin treatment significantly reduced transepidermal water loss, lowered skin surface pH, and increased stratum corneum hydration in a subacute murine allergic contact dermatitis model. Together, these results suggest that topical application of apigenin could provide an alternative regimen for the treatment of dermatitis.